2017
DOI: 10.18203/2349-3933.ijam20171059
|View full text |Cite
|
Sign up to set email alerts
|

A study on effect of strain-counterstrain in plantar fasciitis

Abstract: Background: Bipedal locomotion is a unique feature of human beings and has the advantage of upright mobility. Hence, foot becomes the most important weight loading structure and gets the maximum pressure per unit area. Plantar fasciitis is a painful inflammatory process of the plantar fascia, the connective tissue on the sole of the foot. Thus a study was conducted to determine the effect of strain-counterstrain in plantar fasciitis.Methods: 30 individuals aged between 18-35 years both male and female with pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The plantar fascia is a strong flat band, lies superficial to the intrinsic plantar foot muscles [36,37]. It is a plantar aponeurosis that connects the heel bone to toes [38].…”
Section: Anatomy and Function Of The Plantar Fasciamentioning
confidence: 99%
See 1 more Smart Citation
“…The plantar fascia is a strong flat band, lies superficial to the intrinsic plantar foot muscles [36,37]. It is a plantar aponeurosis that connects the heel bone to toes [38].…”
Section: Anatomy and Function Of The Plantar Fasciamentioning
confidence: 99%
“…The plantar fascia originates from the medial tubercle of the calcaneus and inserts into the phalanges [38]. The plantar fascia contains three bands: Central, lateral, and medial [37,38].…”
Section: Anatomy and Function Of The Plantar Fasciamentioning
confidence: 99%
“…The caused was usually a biomechanical pressure. [2][3][4][5] The Plantar fascia is a plantar aponeurosis that was located superficially between the muscles of the foot surface. 3,4 The functions of the plantar fascia is to maintain the medial longitudinal arch (MLA) of the foot during gait movement, and as a support for shock absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hariharasudhan and Balamurugan (2014) andKoura et al (2020) reported improvements in lumber exion and extension, as well as lumber exion, in cases of acute LPB. Also, Ibáñez-García et al(2009) discovered that applying SCS to trigger points in the masseter muscle made active mouth opening better, andPawar et al (2017) discovered that people with plantar fasciitis had an increase in their ankle dorsi exion range.In 2014, Mohamed and El Shiwi found that applying SCS only to the quadratus lamborum muscle MTrP did not change the way the lumbar spine bent to the right or lifted. However, this study found that SCS had extra effects on bending to the right only.…”
mentioning
confidence: 99%
“…Interestingly, it has been demonstrated that SCS can lessen pain in a variety of conditions, including neck pain (El-Khateeb et al, 2022), masseter muscle trigger points (Ibáñez-García et al, 2009), bilateral hip pain (Wong & Schauer-Alvarez, 2004), and plantar fasciitis (Pawar et al, 2017).disability and enhances daily living activities, which is the cause of this improvement(Cheatham et al, 2016). SCS effectively restores pain-free motion and tissue exibility, thereby improving functional disability(Ali et al, 2015),(Dayanır et al, 2020),(Ahmed et al, 2021), and(Pawar et al, 2017). They also documented this function's notable improvement.…”
mentioning
confidence: 99%